The storage battery and its uses - Coburn, Clay Ephraim (My University, 1891)
Introduction: The advances made in Electrical Science within the last half century have surpassed the prophecies of the most liberal; and this is especially true in the production of strong electric currents for immediate consumption. But the means of storing such currents have been limited. However, within the last ten years such suggestions and improvements have been made as to render such a thing both possible and practical. We will attempt to give in the following a brief account of the earlier discoveries with their subsequent improvements, and to show how they are practically valuable. It has been observed that when two platinum plates are disconnected from a battery and put in circuit with a galvanometer that the presence of an electric current is indicated, flowing in the opposite direction from that in the battery. This phenomenon was studied by scientists living in the early part of the present century. Their explanation was that oxygen had been condensed on the positive plate and hydrogen on the surface of the negative. The result of this was to produce two electromotors, developing a current opposed to the direction of the original one.
Citation: Coburn, Clay Ephraim. The storage battery and its uses. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Electrical engineering; Battery; Secondary current; Invention; Theses; Manuscripts (documents)